2019
DOI: 10.13189/ujer.2019.070408
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Prospective Teachers' Curriculum Literacy Levels in Terms of Reading and Writing

Abstract: This research aims to explore prospective teachers' curriculum literacy in terms of several variables. The research has utilized the cross-sectional survey model, which is one of the descriptive survey models. The research sample holds a total of the fourth-grade 383 prospective teachers who study at teacher training programs and who have been selected by simple random sampling method. This research has been collected through personal information form and curriculum literacy scale. Descriptive statistics and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 8 publications
3
17
0
7
Order By: Relevance
“…In addition, they were able to integrate all these associations into the teaching process. This situation is in parallel with the studies (Aslan, 2019;Çetinkaya & Tabak, 2019;Kızılaslan et al, 2019;Kahramanoğlu, 2019;Erdem & Eğmir, 2018) that included classroom teachers or pre-service teacher studying in the classroom teaching department in the study group and found their education program literacy levels to be medium-sufficient.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, they were able to integrate all these associations into the teaching process. This situation is in parallel with the studies (Aslan, 2019;Çetinkaya & Tabak, 2019;Kızılaslan et al, 2019;Kahramanoğlu, 2019;Erdem & Eğmir, 2018) that included classroom teachers or pre-service teacher studying in the classroom teaching department in the study group and found their education program literacy levels to be medium-sufficient.…”
Section: Discussionsupporting
confidence: 55%
“…Her ne kadar kendi bilgileriyle ilgili algıları orta düzeyde çıkmış olsa da araştırma sonucunda öğretmen bilgileri "Çok katılıyorum" düzeyinde çıkmıştır. Alan yazınına bakıldığında da öğretmenlerin eğitim programı bilgi düzeylerinin genel olarak yüksek seviyede ve kabul edilir düzeyde olduğu belirlenmiştir (Kahramanoğlu, 2019;Aslan, 2019;Aslan ve Gürlen, 2019). Öğretmenlerin eğitim programlarını bilmeleri ve bu alanda kendilerini geliştirmiş olmaları aynı zamanda yeterliliklerinin de gelişmesine katkı sağlamıştır.…”
Section: Sonuç Tartişma Ve öNeri̇lerunclassified
“…Örneğin, programda öne çıkan felsefi yaklaşımın izlerini algılayabilme, öğrencinin nasıl öğrendiğiyle ilgili öne çıkan psikolojik yaklaşım/ları açıklayabilme, programın uygulandığı toplumun kültürel yapıyla uyumunu değerlendirebilme, temel ve alana özgü becerilerin hangi kazanım/larla ilişkili olduğunu açıklayabilme, kazanımların alanına ve düzeyine uygun yöntem, teknik ve değerlendirme yaklaşımı belirleyebilme, programın genel amaçları ve temelleri çerçevesinde özgün ders palanı tasarlayabilme gibi beceriler öğretmenlerin öğretim programı okuryazarlığı konusunda sahip olması gereken becerilerden bazıları olduğu söylenebilir. İlgili literatür incelendiğinde öğretim yada eğitim programı okuryazarlığı konusunda doğrudan çalışmaların (Aslan, 2019;Aslan ve Gürlen, 2019;Bolat, 2017;Erdem ve Eğmir, 2018;Keskin ve Korkmaz, 2017; Süral ve Dedebali, 2018) olduğu ve sayılarının son yıllarda arttığı gözlemlenmektedir. İlgili araştırmalar, genel olarak, öğretmenlerin veya öğretmen adaylarının program okuryazarlık düzeylerinin incelenmesi konusunda olduğu görülmektedir.…”
Section: Introductionunclassified